Financial integration, bank performance and economic growth in Africa - Banyen, Kannyiri Thadious (Graduate School of Business (GSB), 2019)
The finance-growth literature identifies financial integration as a vital catalyst for driving the growth performance of both nascent and advanced economies. Financial integration is viewed as a process by which technology and capital is mobilized and efficiently distributed across national borders to enhance consumption, investments and output growth. However, the benefits of financial integration for economic growth are not unanimous and sometimes evade even the most advanced economies. To promote economic growth, financial integration is required to stimulate competition and efficiency in domestic banking markets without eroding bank profitability or stability. Understanding the effects of deeper financial integration on the conduct and performance of banks and economic growth therefore forms the central theme of this thesis. The study employs several panel data estimation methods to test these hypotheses using data from 405 banks across 47 African countries over the period 2007-2014 and compares the results for five sub-regional markets. The findings reveal that deeper financial integration has significant positive effects on overall bank profitability in Africa. Specifically, the study finds that financial freedom and cross-border banking enhance bank profitability in Africa and across the regional economic communities. The study finds that higher operating cost in the 2007-2014 period reduced bank return on assets but increased overall bank profitability. This reflects the need for banks in underdeveloped banking markets to increase their diversification, expansion and advertising costs in periods of integration and rising competition to ensure overall profitability. The study also finds a direct negative relationship between deeper financial integration and competition changes on bank stability. However, the findings support a U-shaped relationship between competition and bank stability, suggesting that beyond certain thresholds, higher competition will induce greater stability in Africa‘s banking markets. This study, therefore, identifies deficiency of competitiveness as a fundamental variable hindering emerging markets from enjoying the stability benefits of financial integration. Quality regulation and control of corruption are also identified as vital factors for improving bank stability in Africa. The study further shows that financial integration enhances competition, efficiency and bank lending behavior in Africa, resulting in banking convergence in Africa and the regional economic communities. In examining the causal nexus between competition and bank efficiency, the results support the quiet-life hypothesis in Africa, especially in the EAC and reject the quiet-life hypothesis in the AMU and ECCAS sub-regions. The study further finds evidence of the efficient-structure hypothesis in Africa, especially in the AMU and SADC sub-regions. Also, though the study finds no significant nexus between financial integration, bank lending and economic growth in Africa, the evidence supports the feedback hypothesis in the EAC while the supply-leading hypothesis is supported in the AMU, ECCAS and ECOWAS sub-regions. Also, while a positive causal nexus from financial integration to economic growth exist in the AMU sub-region, this relationship is negative in the ECCAS sub-region. Overall, the results suggest that the effect of financial integration on bank performance and economic growth vary significantly across the regional economic communities of Africa. It is, therefore, imperative for bank managers, regulators and policy makers to pursue tailored interventions for each regional economic community while exploiting opportunities for inter-REC collaborations and peer-learning for Africa‘s gross integration and growth.